KARAKTERISTIK AIR LIMBAH INDUSTRI TEMPE (STUDI KASUS: INDUSTRI TEMPE SEMANAN, JAKARTA BARAT) - Matius R R Batistuta Pakpahan; Ratnaningsih Ruhiyat; Diana Irvindiaty Hendrawan (Jurnal Lingkungan dan Kota, 2021)
Tempe is one of the traditional Indonesian foods that have liked by people for a long time. In the tempe processing process, besides soybeans, water is also one of the raw materials that has an important role because water is used in almost every production process: Boiling, Soaking, Washing, and Fermenting. To process 1 kg of soybeans into tempe requires 24.28 liters of water where the boiling process requires 7.02 liters of water, 4.36 liters of soaking, 7.64 liters of washing, and fermentation requires 5.26 liters of water. Tempe production also produces waste water that is bad for the environment where in all the water used in the production process is directly disposed of without being processed first. The quality standard for tempe processed waste is regulated in the Regulation of the Minister of the Environment of the Republic of Indonesia No. 5 of 2014 with 3 main parameters, namely BOD with levels of 150 mg/l, COD 300 mg/l, TSS 100 mg/l. Wastewater produced by tempe production contains BOD 4146.50 mg/l, COD 32297.71 mg/l, and TSS 0.75 mg/l. The wastewater produced by tempe production exceeds the government quality standard, but in the production of tempe, the waste water is not treated but is discharged into water bodies.